Bread in Moroccan Culture: Sacred Symbol and Nutritional Staple - Youssef Mir (International Journal of Scientific Research and Innovative Studies, 2024)
Bread is not merely a food item in Moroccan society; it holds deep cultural and symbolic status that transcends its role as a dietary staple. Unlike other foods, bread is revered, with unique rituals that reflect its sacredness. This article reviews bread’s role in Moroccan society, highlighting its central place in daily life, historical roots, and contemporary relevance. The analysis examines religious, nutritional, and psychological aspects surrounding bread in Morocco, with comparisons to other cultural practices. Through a synthesis of studies from anthropology, nutrition, and cultural psychology, we provide a holistic understanding of bread’s unique position in Moroccan society. Keywords: Moroccan culture, bread, cultural symbolism, food ritual, anthropology, nutrition, sustenance, reverence. Received Date: September 14, 2024 Accepted Date: October 12, 2024 Published Date: November 13, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/205 DOI: https://doi.org/10.5281/zenodo.14148242